Analysis Of The Effect Of Personal Sales And Product Quality On Consumer Purchase Decisions - Elisabeth Nainggolan; Muammar Rinaldi; Muhammad Bukhori Dalimunthe (Institute of Computer Science (IOCS), 2022)
This study aims to determine the effect of Personal Sales on Purchase Decisions at PT. Kao Indonesia, knowing the effect of Product Quality on Purchase Decisions at PT. Kao Indonesia, knowing the effect of Personal Sales and Product Quality on Purchase Decisions at PT. Indonesian Kao. The research population that will be used in the study are all consumers who made purchases of the company's products at Brastagi Supermarket Gatot Subroto during the 2020 period as many as 47,529 consumers. By using the Slovin formula with an error rate of 10%, the number of samples obtained is 100 respondents. The analysis of this study used the Multiple Linear Regression test. The results showed that Personal Selling partially has a positive and significant influence on Purchase Decisions at PT. Kao Indonesia, Product Quality partially has a positive and significant influence on Purchase Decisions at PT. Indonesian Kao.